2001
DOI: 10.1046/j.1570-7458.2001.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of juvenile hormone on caste determination and colony processes in the bumblebee Bombus terrestris

Abstract: To investigate the role of juvenile hormone (JH) in caste determination, first and second instar larvae of Bombus terrestris were topically treated with one of three doses (2, 10, or 20 μg/larva) of JH dissolved in acetone. Treated larvae belonged to very young colonies that had just been started by their queen. Therefore, all larvae were supposedly destined to develop into workers. Our study demonstrates that a single application of JH in the first or second instar can lead to the development of queens and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…II, III). This was consistent with the observed temporal link between the timing of queen production and the competition point in B. terrestris (Duchateau and Velthuis, 1988;Bloch, 1999;Bortolotti et al, 2001;Alaux et al, 2004) and, specifically, with the proposal that workers use the onset of queen development as a cue to commence egglaying (Crespi, 1992;Kukuk, 1992;Cnaani et al, 2000;Bourke and Ratnieks, 2001;Duchateau et al, 2004;Alaux et al, 2006). However, we also found that, in most colonies in Experiment 1, workers in the queenless compartments exhibited aggression and egglaying even though no new queens were developing (Tabs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…II, III). This was consistent with the observed temporal link between the timing of queen production and the competition point in B. terrestris (Duchateau and Velthuis, 1988;Bloch, 1999;Bortolotti et al, 2001;Alaux et al, 2004) and, specifically, with the proposal that workers use the onset of queen development as a cue to commence egglaying (Crespi, 1992;Kukuk, 1992;Cnaani et al, 2000;Bourke and Ratnieks, 2001;Duchateau et al, 2004;Alaux et al, 2006). However, we also found that, in most colonies in Experiment 1, workers in the queenless compartments exhibited aggression and egglaying even though no new queens were developing (Tabs.…”
Section: Discussionsupporting
confidence: 90%
“…There is a tight temporal link between the onset of Corresponding author: A.F.G. Bourke, a.bourke@uea.ac.uk * Manuscript editor: Stan Schneider worker reproduction and queen production, with the competition point predictably occurring c. 10 days after the queen lays the first diploid eggs that will develop as new queens (Duchateau and Velthuis, 1988;Bloch, 1999;Bortolotti et al, 2001;Alaux et al, 2004). A variety of evidence supports pheromonal queen regulation of worker reproduction and queen development, but the exact mechanisms are not fully resolved (Crespi, 1992;Kukuk, 1992;Bloch and Hefetz, 1999a;Cnaani et al, 2000;Bourke and Ratnieks, 2001;Duchateau et al, 2004), partly because the experimental evidence is not always consistent across different studies.…”
Section: Introductionmentioning
confidence: 99%
“…This is, again, in line with the effects of precocene in other solitary insects (Lee and Tan, 1980;Samaranayaka-Ramasamy and Chaudhury, 1981;Deb and Chakravorty, 1982;Socha and Hodkova, 1983;Li et al, 1993;Kumar and Khan, 2004). This also confirms the gonadotropic function of JH in B. terrestris that was until now based on correlations (Roseler, 1977;Van Doorn, 1989;Bloch et al, 1996;Bloch et al, 2000b;Bortolotti et al, 2001;Shpigler et al, 2010), and provides direct evidence for the necessity of JH for oocyte development and egg laying in queenless B. terrestris workers. Similar conclusions were reached by a recent study performing allatectomy in B. terrestris workers (Shpigler et al, 2014), supporting the effect of precocene.…”
Section: Research Articlesupporting
confidence: 82%
“…Queen production has been suggested to be related to high worker to larva ratios (Cumber, 1949; ment of larvae directly. Recent work on the physiological mechanisms underlying caste differentiation in B. terrestris suggests, however, that caste development is not under worker control (Cnaani et al, 1997Cnaani and Hefetz, 2001;Hartfelder et al, 2000, Bortolotti et al, 2001. These studies provide evidence for a direct influence of the queen's presence on caste-specific endocrine events during the larval development, and that size dimorphism is primarily a result of different development duration.…”
Section: Introductionmentioning
confidence: 77%